1995
DOI: 10.1007/bf01957508
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of complex I deficiency: Peripheral neuropathy during dichloroacetate therapy

Abstract: A therapeutic trial with polyvitamins and dichloroacetate (DCA) in combination with thiamine in a 13-year-old girl with complex I deficiency is reported. The polyvitamin therapy included thiamine, riboflavin, ascorbate, coenzyme Q 10 and carnitine. This therapeutic regine was used over a period of 17 months without any effect. Although DCA lowered the lactate concentration in blood and CNS--measured by magnetic resonance spectroscopy--no clinical benefit was achieved. After 20 weeks of DCA therapy a distal pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
1
20
1
Order By: Relevance
“…Similar observations were made in other cases of mitochondrial disease phenotypes [10,45] underlining the potential of MRS for monitoring treatment response on a quantitative level. Treatment with oral Cr supplementation was monitored in both GM lesions and NAGM in patient 5, in this case without consistent indicators of a beneficial effect [18].…”
Section: Discussionsupporting
confidence: 73%
“…Similar observations were made in other cases of mitochondrial disease phenotypes [10,45] underlining the potential of MRS for monitoring treatment response on a quantitative level. Treatment with oral Cr supplementation was monitored in both GM lesions and NAGM in patient 5, in this case without consistent indicators of a beneficial effect [18].…”
Section: Discussionsupporting
confidence: 73%
“…In general, dichloroacetate therapy is tolerated well in most cases and may lead to short-term improvement. However, long-term use may induce peripheral neuropathy, and there have been no studies showing clear benefits of long term DCA usage on the overall disease prognosis (Kurlemann et al 1995;Kaufmann et al 2006). A promising future option could be phenylbuytrate, which has a comparable mode of action but potentially less side effects (Ferriero et al 2013).…”
Section: Dichloroacetate Therapymentioning
confidence: 98%
“…116,117 In a recent study examining hyperthyroidism and cardiac hypertrophy in rats, DCA administration completely reversed reductions in PDH flux, and significantly reduced cardiac hypertrophy without affecting cardiac output. 118 Although human data are limited due to the chronic neurotoxicity of DCA, 119-121 one study in patients with angina and coronary artery disease revealed that infusion of DCA during left heart catheterization was associated with increased stroke volume and myocardial efficiency index (LV work/myocardial oxygen consumption). 122 …”
Section: Metabolic Therapies For Heart Failurementioning
confidence: 99%